Shoulder Dislocation in Children. A Case Presentation - Eduardo García Pérez; Yovanny Ferrer Lozano; Yanett Morejón Trofimova (Medisur)
In pediatric age, epiphysis fractures are more common that the sprains  or dislocations due to the presence of bone tissue that can undergo a greater elastic deformation, a thick periosteum, stabilizer and ligaments with greater resistance to breakage than growth cartilage. We report the case of a white skinned male of 2 years old that was treated in our department because of a right scapulohumeral dislocation. This was reduced and immobilized for three weeks. At five weeks of development the affected shoulder presented the same range of movements than contralateral shoulder.